Safety, Tolerability and Pharmacokinetics of Single and Multiple Ascending Doses of Benfotiamine in Healthy Subjects - Sheng, Lei (Drug Des Devel Ther, 2021)
PURPOSE: Safety, tolerability and pharmacokinetics of single and multiple ascending doses (SADs/MADs) of benfotiamine were assessed after oral administration in two randomized, double-blind, placebo-controlled, phase I trials. METHODS: Healthy subjects were sequentially enrolled into one of five SAD (150–1200 mg) or three MAD (150, 300 or 600 mg) cohorts. In SAD study, each cohort of 12 subjects (n = 10, active; n = 2, placebo) were administrated once-daily doses. In MAD study, each cohort of 16 subjects (n = 12, active; n = 4, placebo) were administrated once-daily on day 1 and twice-daily on day 4–9, followed by a single morning dose on day 10. RESULTS: In the SAD study, the median time to reach maximum concentration (T(max)) arrived 1.0 to 2.0 h for thiamine (TM), 3.5 to 8.0 h for thiamine monophosphate (TMP), and 8.0 to 24.0 h for thiamine diphosphate (TDP) after administration of benfotiamine. The area under concentration-time curve from 0 to last measurable concentration (AUC(0-t)) or maximum observed concentration (C(max)) of TM, TMP, and TDP was less or more dose proportional over the single dose studied except C(max) of TM. Food consumption did not increase the level of TM and TDP at baseline. TM exhibited a relatively long elimination half-life (t(1/2)) in all doses studied, resulting in accumulation ratio (Rac) of 1.96 to 2.11 and accumulation ratio based on C(max) (Rac, (Cmax)) of 1.60 to 1.88 following 7 days of multiple dosing. Comparable accumulation results were also obtained for TDP after multiple dosing. The incidence and severity of adverse events (AEs) were similar between benfotiamine and placebo. The commonly reported drug-related AEs were increased ALT and urinary WBC. CONCLUSION: Both SAD and MAD studies of benfotiamine in healthy subjects were safe and well tolerated. TM and TDP exhibited moderate accumulation on repeated administration of benfotiamine.